2015
DOI: 10.2106/jbjs.m.01496
|View full text |Cite
|
Sign up to set email alerts
|

Computer Navigation for Total Knee Arthroplasty Reduces Revision Rate for Patients Less Than Sixty-five Years of Age

Abstract: Computer navigation reduced the overall rate of revision and the rate revision for loosening/lysis following total knee arthroplasty in patients less than sixty-five years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
128
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(137 citation statements)
references
References 39 publications
2
128
0
5
Order By: Relevance
“…In contrast to the hip systems, most studies in the knee arthroplasty robotic surgery have showed decreased time required to make femoral cuts, compared with the standard computer navigation techniques. 12 There was no difference in the overall tourniquet time. There are no randomised clinical trials or long-term studies to show any advantage of these systems over the conventional method of performing knee arthroplasty.…”
Section: Robotic Applicationsmentioning
confidence: 90%
“…In contrast to the hip systems, most studies in the knee arthroplasty robotic surgery have showed decreased time required to make femoral cuts, compared with the standard computer navigation techniques. 12 There was no difference in the overall tourniquet time. There are no randomised clinical trials or long-term studies to show any advantage of these systems over the conventional method of performing knee arthroplasty.…”
Section: Robotic Applicationsmentioning
confidence: 90%
“…The Australian registry reported a reduced revision rate for computer-navigated procedures in patients less than 65 years of age, and there was a reduction in revision rate due to loosening (de Steiger et al. 2015), but only with adjustment for age and sex. In a group of equivalent age, the arthroplasty registry in New Zealand found a trend of a higher revision rate for Triathlon implants inserted with computer-assisted navigation (not statistically significant) (Roberts et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study from the Australian Orthopaedic Association National Joint Replacement Registry found a lower cumulative revision rate for computer navigation in patients less than 65 years (de Steiger et al. 2015). …”
mentioning
confidence: 99%
“…Despite numerous publications providing supporting evidence of the advantages of this technology over conventional instrumentation, knee arthroplasty navigation has yet to become mainstream 14. Several reasons have been cited, including cost, learning curve, additional incisions for pin sites, increased operating room time, technical difficulty and lack of evidence that clinical outcomes are improved 15 16…”
Section: Introductionmentioning
confidence: 99%
“…de Steiger et al 14 demonstrated a clinical benefit in CAS TKA in patients younger than 65 years old.…”
mentioning
confidence: 99%